PENINGKATAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MELALUI LESSON STUDY - Sriyati, Mrs Siti (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2007)
This research was done to investigate impact of lesson study in order to improveteachers professionalism and the quality of teaching learning process in Biology.Although lesson study has been conducted since the year of 2005 at numerousschools- in Bandung, information on how far such activity does give impact toteacher as instructoi and teacher as observer has not been covered. The researchwas undertaken by spreading questions to the instructor as well as the observer.Furt5ermore, quaiity-of teaching learning process in the school was observed atSMP Lab. School and SMA Lab. School UPI. The research resulted in insight thatthrough lesson study, teachers both served as instructor and observer can improvesuch competency as pedagogy, professional, personality, social as clearlyinclicated in ., UU Guru dan Dosen l,1o. 14 Tahun 2005". However, for thoseteachers as observers, competency of pedagogy has not been significantlyexplored. Both the instructors and observers have not entirely user their KBM(teaching learning process) to conduct PTK (classroom action research). InuOOitionl the KBM ionducted in lesson study can improve quality of teachingleaming process in the classroom based upon good interaction between studentsand te;hers as well as among students (in or out the groups) during discussionand percentage of students who actively learned. Through model teachinglearning pro"Jrr tleveloped in lesson study, students are trained to improve theirability i-n scientific work and to connect biology concept to its application in dailylile using local materialsKeyword : Teachers professionalism, lesson study, KBM (Teaching learningprocess),PTK (Classroom action research)